Two-stage water resources allocation negotiation model for transboundary rivers under scarcity - Wu, Xia; He, Weijun; Yuan, Liang; Kong, Yang; Li, Renyue; Qi, Yuzhi; Yang, Dongquan; Degefu, Dagmawi Mulugeta; Ramsey, Thomas Stephen (Frontiers in Environmental Science, 2022)
Population growth, industry development, accelerated urbanization, and global warming, combined with the rising scarce global water resources, are increasing the frequency of water conflicts in transboundary river basins. Riparian countries usually allocate water resources through cooperative negotiation, and these negotiations always have two stages: creating value and claiming value. In this article, the bankruptcy theory and bargaining games are used to construct a two-stage water resources allocation negotiation model. A Nash-bargaining game model is used for the initial allocation, followed by an adjustment stage which considers factors such as water circumstances, water satisfaction, water risk, and water efficiency. The proposed method is applied to allocate the contested water capital of the Tigris-Euphrates River. This gives initial allocation to Turkey, Syria, and Iraq of 30.00%, 22.00%, and 48.00%, respectively, and adjusted allocation of 24.98%, 21.30%, and 53.72%. Through collective bargaining and group negotiation, the stability and acceptability of allocation are effectively improved, absolute egalitarianism and utilitarianism are both avoided, and instead objectivity and fairness are emphasized in the water resources allocation process.